Manajemen Kelas Dalam Meningkatkan Motivasi Belajar Siswa - Citra Aulia Uzliva; Albi Fadillah (STAI Publisistik Thawalib Jakarta, 2023)
The aim of the research is to describe classroom management and its impact on student learning motivation. The research method is qualitative through a case study approach. Data collection techniques using interviews, documentation, and observation. Data analysis techniques with reduction, data presentation, and conclusions. Data validity techniques using triangulation of sources and techniques. The research results show (1) classroom management: (a) planning: making semester plans, making motivational words, praying before learning, taking student attendance, and arranging seating. (b) organizing: forming a class structure and scheduling class cleaning pickets. (c) implementation: the learning process is going well. (d) controlling: asking and ensuring the learning process. (2) impact: students are happy, feel at home in class, don't joke around, and participate in learning well.